Improving Mountain Pine Beetle Survival Predictions Using Multi-Year Temperatures Across the Western USA - Christopher Bone (Forests, 2019)
Global climate change has led to an increase in large-scale bark beetle outbreaks in forests around the world, resulting in significant impacts to forest ecosystems, timber economies, and forest-dependent communities. As such, prediction models that utilize temperature for estimating future bark beetle locations and consequential tree mortality are critical for informing forest management decision-making in an attempt to mitigate and adapt to pending and current outbreaks. This is especially true for physiological models that account for the effects of overwinter temperatures on bark beetle survival, as seasonal temperatures, specifically during winter months, exert the greatest impact on bark beetle mortality during various stages of life cycle development. Yet, how temperature observations are used to predict bark beetle survival can significantly under- or over-estimate the role that temperature variability plays in annual tree mortality, especially under current climate change trajectories. This study evaluates how representations of winter temperature influence bark beetle survival estimates. Using the recent outbreak of mountain pine beetle (Dendroctonus ponderosae Hopkins) across the western USA as a case study, single-year to decade-long winter temperature averages were used as inputs into a physiological beetle survival prediction model, the results of which were compared against beetle-induced tree mortality observations using temporal autoregressive models. Results show that using longer-term survival averages of seven to ten years significantly increases the likelihood that temperature alone can predict general levels of beetle survival and hence beetle-induced mortality. These findings demonstrate the importance of considering the role of long-term temperature observations when forecasting bark beetle outbreaks, and that year-to-year temperature variability may be constrained in predicting beetle survival during outbreak periods.